THE THEORY AND PRACTICE OF SIMULTANEOUS INTERPRETING: PROBLEMS AND SOLUTIONS (KELAJAK SARI YANGI O’ZBEKISTON: ILM-FAN, TEXNOLOGIYA VA TA’LIM, 2026)
This article analyzes the theoretical foundations of the simultaneous interpreting process, its practical complexities, and the challenges faced by interpreters. It also proposes effective solutions to these problems through modern technologies and methodological approaches.